Thermal Elastohydrodynamic Lubrication Analysis of Automotive Differential Bevel Gear Under Differential Condition - Cong Wei; Youqiang Wang; Yabo Zhou; Shenwen Long (Jixie chuandong)
In order to study the meshing thermal characteristics of the differential bevel gear under differential conditions， based on the thermal elastohydrodynamic lubrication theory， an unsteady thermal elastohydrodynamic lubrication model of straight bevel gears is established， and the temperature field of planetary gear is analyzed under differential condition. Firstly， the thermal characteristics of planetary gear and half-shaft gear under non-Newtonian fluids are studied. Secondly， the temperature field changes of planetary gear under differential conditions are studied with different tooth width and modulus. Finally， the temperature field variation of planetary gear with different rotational speed is studied. The results show that the temperature distribution of planetary gear across tooth width direction is different， the maximum temperature of the planetary gear body increases with the increase of tooth width， and decreases with the increase of the modulus. The temperature of the contact area between differential planetary gear and half-shaft gear increases as the rotational speed increases. This study provides a theoretical basis for the design of differential bevel gear lubrication.